1950
DOI: 10.1002/zaac.19502620114
|View full text |Cite
|
Sign up to set email alerts
|

Verlust der Austauschfähigkeit von Lithiumionen an Bentonit durch Erhitzung

Abstract: Bentonit mit austauschfähigen Li‐Ionen verliert das innerkristalline Quellvermögen zwischen 105 und 125° C. Die OH‐Ionen der Silikatschichten bleiben noch über 200° erhalten. Es entsteht also bei 125° ein Glimmer niederster Ordnung. Bei 105° hat bereits die Hälfte der Li‐Ionen die Austauschfähigkeit verloren. Auch bei H‐, Ca‐ und Na‐Ionen beginnt dieser Verlust vor dem Verschwinden der innerkristallinen Quellung, aber bei jeweils höheren Temperaturen. Diese Verminderung der Menge der austauschfähigen Kationen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
153
0
3

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 340 publications
(159 citation statements)
references
References 3 publications
3
153
0
3
Order By: Relevance
“…In addition to the vast variety of available smectites with different CECs, it is possible to reduce the CEC by the thermal treatment of Li exchanged forms (HofmannKlemen Effect). 19) It has been recognized that the CEC is a key factor to determine many important properties of smectites and their intercalation compounds. 20) The variation of CEC has been used to control the distances of adjacent interlayer cations, resulting in the controlled molecular sieving functions 21), 22) of pillared clays and photoprocesses of adsorbed cationic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the vast variety of available smectites with different CECs, it is possible to reduce the CEC by the thermal treatment of Li exchanged forms (HofmannKlemen Effect). 19) It has been recognized that the CEC is a key factor to determine many important properties of smectites and their intercalation compounds. 20) The variation of CEC has been used to control the distances of adjacent interlayer cations, resulting in the controlled molecular sieving functions 21), 22) of pillared clays and photoprocesses of adsorbed cationic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…The expansion of the 001 spacing of smectite to 17 ,~ after K § saturation and ethylene glycolation indicated a small layer charge, whereas nonexpansion to that spacing indicated a large layer charge. The location of the layer charge was detected by the Hofmann-Klemen and Greene-Kelley Li-test (Hofmann and Klemen, 1950;Greene-Kelley, 1955;Schuttz, 1969;Howard, 1981;Komarneni and Breval, 1985) by Li + saturation, heat treatment at 250~ for 8 hr, glycerol solvation (glyceration), and XRD of oriented samples. The expansion of the 001 spacing to ~ 18/k on Li + saturation, heat treatment, and glyceration indicated that the charge was located in the tetrahedral sheet, whereas non-expansion indicated that the charge was located in the octahedral sheet.…”
Section: Methodsmentioning
confidence: 99%
“…The CEC is directly related to layer charge in pure monomineralic samples, but not in samples with a mixed mineralogy. The decrease in montmorillonite CEC/layer charge by lithium/thermal treatment is termed the HofmannKlemen effect after Hofmann & Klemen (1950). Lithium charge reduction makes it possible to vary the CEC/layer charge of a particular clay sample and examine the effect of layer charge on other properties.…”
Section: Preparation Of Reduced-charge Claysmentioning
confidence: 99%